2007
DOI: 10.1017/s0022109000003318
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Liquidity and Firm Dividend Policy

Abstract: We provide evidence of a link between firm dividend policy and stock market liquidity. In the cross section, owners of less (more) liquid common stock are more (less) likely to receive cash dividends. Predictions of the proportion of dividend payers based on 1963–1977 cross-sectional estimates account for most of the declining propensity of firms to pay dividends as documented by Fama and French (2001). Furthermore, historic liquidity is an important determinant of dividend initiations and omissions. Finally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
62
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(87 citation statements)
references
References 58 publications
20
62
4
1
Order By: Relevance
“…Blum and Keim (2012) showed that institutional participation in the US stock market played an ever increasing role in explaining cross-sectional variation in stock market illiquidity. Banerjee et al (2007) found some evidence that sensitivity of firm value to innovations in aggregate liquidity declines after dividend initiations. Indeed, Baker and Wurgler (2004) presented significant evidence that the payout policy of the firm was related to the liquidity of its common stock.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Blum and Keim (2012) showed that institutional participation in the US stock market played an ever increasing role in explaining cross-sectional variation in stock market illiquidity. Banerjee et al (2007) found some evidence that sensitivity of firm value to innovations in aggregate liquidity declines after dividend initiations. Indeed, Baker and Wurgler (2004) presented significant evidence that the payout policy of the firm was related to the liquidity of its common stock.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, more mature firms with higher retained earnings to equity ratio have higher probability of paying dividends. Moreover, in line with Banerjee et al (2007) and Rozeff (1982), firms with higher stock liquidity and insider ownership have lower www.ccsenet.org/ijef…”
Section: Resultsmentioning
confidence: 79%
“…Besides, Banerjee, Gatchev, and Spindt (2007) examine the relationship between stock liquidity and dividend policy with a sample of a sample of NYSE and AMEX listed firms from 1963 to 2003. Their findings show that after controlling other firm characteristics, firms with higher stock liquidity are less likely to pay dividends.…”
Section: Decisions Of Paying or Not Paying Dividendsmentioning
confidence: 99%
“…Therefore I use the company earned/contributed equity mix defined as retained earnings to the book value of total equity as a control variable. (Banerjee, Gatchev, & Spindt, 2007) find that firm stock turnover is related to payouts so I include it as a control. I include the ratio of firm debt to assets as a control because Jensen (1986) argues that debt can substitute for payouts as discipline for management.…”
Section: Datamentioning
confidence: 99%